ENVIRONMENTAL GEOCHEMICAL AND MINERALOGICAL STUDY OF THE PELLANA LIGNITE (PREFECTURE OF LAKONIA) - Χατζηαποστόλου Α.; Καλαϊτζίδης Σ.; Παπαζησίμου Σ.; Χρηστάνης Κ.; Βάγιας Δ. (Bulletin of the Geological Society of Greece, 2004)
The aim of this study is to estimate the environmental impacts in case of exploitation the Pellanalignites for power generation. The object of the study is to predict the element mobility during lignite combustion using mineralogical and geochemical data from bulk-lignite samples and their ashes of two cores from this area. The mineralogical determinations on the ashes revealed that quartz, K-feldspars and illitemicas are the major mineral phases contained in the lignite. The identification of anhydrite in ashes implies the presence of gypsum, althought neoformation of anhydrite from organic associated with Ca+2 and SO42 can not be excluded. These minerals correspond to primary phases. Oxides and hydroxides occur subordinately and probably represent minerals that do not correspond to primary phases. The results of the elemental analysis show that the major elements (>1000 ppm) are AI, Fe, Ca, Mg and Κ in the bulk samples of both cores. Minor elements (100-1000 ppm) are Na, Mn and Ba, while the concentrations of Be, Bi, Cd, Ce, Co, Cs, Cu, Eu, Ga, Hf, La, Li, Lu, Mo, Nb, Nd, Pb, Rb, Sb, Se, Sm, Sn, Sr, Tb, Te, Th, TI, U, Y, Yb and Zr do not exceed 100 ppm. The concentrations of many elements like As, Ba, Cr, Ni, V and Zn have a wide range among the bulk samples. In order to assess the geochemical affiliation of the studied elements, R-type factor analysis was applied on the element contents of bulk lignite and ash. The elements Ca, S, V, As, Μη, Mo, Na, Sb, Hf, Zr and U provide both organic and inorganic affiliations, while Se and Nb provide organic affiliations. To approach the mobility of each trace element, the relative enrichment factor (RE) was calculated. The most depleted trace elements according to RE mean (<0.5) are Hf and Sb, while the elements Se and Ba are moderately depleted (0.7>RE mean>0.5).